Enhancing Quality Assurance in Higher Education through Strategic Library Management and Digital Literacy Initiatives - Nur 'Azah; Juraidah; Hassan Fateh (Journal of Education and Learning Sciences, 2025)
In the era of Education 5.0, higher education institutions are increasingly required to ensure quality assurance mechanisms that promote academic excellence and global competitiveness. Libraries, as knowledge management hubs, play a strategic role in supporting institutional quality by providing access to information, facilitating digital literacy, and enhancing research productivity. This study aims to examine how strategic library management and digital literacy initiatives contribute to strengthening quality assurance frameworks in higher education. Using a library research method, this paper synthesises findings from 52 international journal articles, books, and reports published between 2018 and 2024. The results indicate that universities implementing innovative library management strategies such as the integration of digital repositories, open-access scholarly databases, and user-centred services significantly improve teaching quality, research visibility, and accreditation performance. Furthermore, initiatives to develop students’ and faculty members’ digital literacy competencies contribute to enhanced learning outcomes and institutional ranking. The findings highlight the necessity of integrating strategic library policies with quality assurance systems to meet international accreditation standards and ensure sustainable institutional development.